PENGARUH PERENCANAAN STRATEGIS DAN PENGAWASAN TERHADAP EFEKTIVITAS PENERIMAAN PAJAK GALIAN C DI KABUPATEN KARANGASEM - widayani, Nyoman Suma (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2022)
The Effect of Strategic Planning and Supervision on the Effectiveness of Tax Receipts from Excavation C in Karangasem Regency. The majority of the Karangasem Regency Original Revenue comes from the Excavation C tax The contribution of the Excavation C tax to the PAD of Karangasem Regency is 33.22% (Rp.80,559,954,401.00) of the total PAD of Rp 242,486,180,423.66. This shows the Excavation C tax has a large contribution to the Regional Original Income (PAD) revenue, but there has been a decrease in the Excavation C Tax revenue in 2015-2019, due to leakage of tax revenue and there are Excavation C entrepreneurs have not a permit. The results of the research from multiple correlation test obtained the sig value. F Change of 0.000 <0.005 there is a correlation between strategic planning and supervision of the effectiveness of Galian C tax revenue in Karangasem Regency. Based on the results of the interview, that the strategic planning related to the Excavation C tax revenue in Karangasem Regency has not been implemented according to the predetermined plan, the problems with the performance of the Regional Apparatus Organization which is authorized in the Excavation C tax revenue As well as the supervision of the Excavation Tax revenue. C by BPKAD and Satpol PP of Karangassem Regency, has not been implemented optimally and not able to strengthen a sense of responsibility. Keywords: Effectiveness, Excavation C Tax